Torso injuries after fall from standing-empiric abdominal or thoracic CT imaging is not indicated. Issue 1 (January 2020) - Hagan, Natalie E.; Berdel, Henrik O.; Tefft, Amy; Bernard, Andrew C.
Highlights: Selective torso CT in falls from standing is controversial, and predictive value of physical examination to exclude intervention is unknown. When combined with vital signs, the negative predictive value of abdominal physical exam for intervention was 100%. Of 1, 654 patients in our study, only 24 underwent torso intervention, indicating that intervention in falls from standing is rare. Abstract: Purpose: Falls from standing (FFS) have become the most common mechanism of injury at many trauma centers. Liberal imaging of low energy trauma has questionable value. We hypothesize that torso trauma intervention is rare in the FFS population, and physical examination sufficiently screens for torso injuries needing intervention. Methods: We queried our ACS-verified Level 1 trauma center registry for falls from standing from 1/1/14 to 12/31/16. Exclusion criteria were: falls from height, falls associated with penetrating trauma, lack of an abdominal or chest CT, a Glasgow Coma Scale Score (GCS) less than 15, and surgical intervention at another facility prior to arrival at our center. Demographics, historical details, hemodynamics, injuries, injury severity, procedures, initial vital signs, and outcome were recorded. Results: 1, 654 patients had a FFS during our study period. 728 had an abdominal or chest CT and a GCS of 15 and comprised the evaluable population. Mean age was 56.5 years. 55.8% were female. The mortality rate was 8%. There were 179 chest injuries in 121 patients, and 54 abdominal injuries in 43 patients. 379 patients had a GCS of 15 and underwent thoracic CT, yet only 11 (3%) underwent intervention. The negative predictive value for physical exam was 100% for chest intervention. 349 patients had a GCS of 15 and abdominal CT, yet only 13 (3.7%) underwent procedural intervention. Abdominal physical exam had a negative predictive value of 99.7% for intervention, but when combined with vital signs, the value was 100%. Conclusion: Torso injuries in FFS are rare. Of our study population, 13 abdominal injuries underwent intervention, and 11 chest injuries underwent intervention. Screening patients by physical examination and vital signs is sufficient and safely allows for the use of selective abdominal and chest CT.